2023
DOI: 10.1021/acs.jpcb.2c07266
|View full text |Cite
|
Sign up to set email alerts
|

Flavin Charge Redistribution upon Optical Excitation Is Independent of Solvent Polarity

Abstract: Flavin absorption spectra encode molecular details of the flavin’s local environment through coupling of local electric fields with the chromophore’s charge redistribution upon optical excitation. Translating experimentally measured field-tuned transition energies to local electric field magnitudes and directions across a wide range of field magnitudes requires that the charge redistribution be independent of the local field. We have measured the charge redistribution upon optical excitation of the derivatized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 64 publications
0
0
0
Order By: Relevance
“…Multiple computational studies have investigated the excited-state electronic structure and photophysics of flavin. A nonexhaustive list includes refs , , . A more comprehensive list of computational studies can be found in a recent review article by Kar, Miller, and Mroginski .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple computational studies have investigated the excited-state electronic structure and photophysics of flavin. A nonexhaustive list includes refs , , . A more comprehensive list of computational studies can be found in a recent review article by Kar, Miller, and Mroginski .…”
Section: Discussionmentioning
confidence: 99%
“…Several methods, including semiempirical, TD-DFT, and multireference (often, MR-PT2) methods have been used already to calculate the excited-state properties of flavins. , , For multireference calculations, the issue of active space selection is a recurring theme and a decision is often made that balances computational cost and computational accuracy due to the steep increase in computing time with the size of the active space. Automated protocols to select the active space have been developed by several research groups. , Sayfutyarova and Hammes-Schiffer applied their automated protocol that is based on Hückel theory for the selection of a suitable active space for flavin’s π-conjugated orbitals .…”
Section: Introductionmentioning
confidence: 99%